MENUMBUHKAN BUDAYA HIDUP SEHAT SEKALIGUS MEMBERDAYAKAN MASYARAKAT MELALUI PRODUKSI MINUMAN HERBAL YANG BERNILAI EKONOMI - Erna Haryanti; Dwie Retna Suryaningsih; Koesriwulandari Koesriwulandari; Ristani Widya Inti; Dewa Putra Prassuwito; Agustina Dwi Kartika (Yayasan Education and Social Center, 2023)
Community Service Activities (PKm) are carried out in the area of ​​RT 05 RW 9 Dukuh Kupang Timur, Pakis Village, Sawahan District, Surabaya City with the theme: GROWING A HEALTHY LIVING CULTURE WHILE EMPOWERING COMMUNITIES THROUGH THE PRODUCTION OF HERBAL DRINKS WITH ECONOMIC VALUE. PKm activities aim to motivate the community to live healthy by consuming herbal drinks, as well as being used as a business field, especially for people affected by the Covid 19 pandemic changing their status to beneficiary families. Through this activity the community gains knowledge and skills in producing various kinds of healthy herbal drinks and implementing them as economically productive activities. The objectives of this activity are: a) Motivate the community to have a culture of healthy living. b) Transferring science and technology through counseling activities and entrepreneurship assistance by producing healthy herbal drinks that have economic value. c) Growing innovative and sustainable new entrepreneurs. Activity planning is prepared in a bottom-up manner by applying participatory methods, namely the PRRA and RRA methods, so that the target can synergize with the implementing team in terms of planning, organizing, implementing and evaluating the implementation of these activities Community very enthusiastic which was shown by his enthusiasm to participate in the activity and practice making the healthy drink Secang, Turmeric Tamarind, Rice Kencur, Sinom